Rates of diagnosis and treatment of neurological disorders within a prevalent population of community-dwelling elderly people in sub-Saharan Africa - Felicity Dewhurst; Matthew J. Dewhurst; William K. Gray; Paul Chaote; William Howlett; Golda Orega; Richard W. Walker (Springer, 2019)
Background: The prevalence of neurological disorders in those aged 70 years and over in the Hai district of Tanzania has been previously reported. The following research reports rates of patient's: treatment seeking, diagnosis and treatment within this prevalent population. Methods: All people identified as having at least one neurological disorder in the prevalence study were questioned regarding whether they had sought treatment for their disorder, whether they had had a previous correct diagnosis and whether they were being currently treated. Results: From a background population of 2232 people, 349 people had neurological disorders, of whom 225 (64.5%) had sought treatment for their symptoms. Of the 384 disorders identified in these 349 people, only 14.6% had been diagnosed and only 9.9% were receiving appropriate treatment. Males were significantly more likely to have been diagnosed and were more likely to have been treated appropriately. Conclusions: Levels of diagnosis and treatment were low, with some gender inequality. Reasons for this may include a lack of recognition of the condition within the local population and lack of access to appropriate services. In the absence of effective primary and secondary preventative measures, and effective treatment, the burden of neurological disorders is likely to increase with further demographic ageing.